Sámská historická fonetika II : vokalismus v konfrontaci s jazyky baltsko-finskými a v uralském kontextu - Hofírková, Lucie; Blažek; Václav (2011)
The article consists of three parts. In the first part the vocalic correspondences between Balto-Fennic and Saamic languages are illustrated by 25 examples. In the second part the basic vocalic correspondences between main Uralic branches are demonstrated by 22 examples. In the third part the tables summarizing our results appear.